Implementation of Quantum Error Correction Code on Qubit Superconducting to Improve Quantum Computing Stability - Khan, Jamil; Akhtar, Shazia; Ali, Zara (Yayasan Adra Karima Hubbi, 2024)
The background of this research focuses on the stability of quantum computing, which is a major challenge in the development of quantum technology. Superconducting qubits are known to be prone to errors due to environmental disturbances and noise, which hinders computational accuracy. Quantum error correction code (QECC) emerged as a solution to solve the problem by detecting and correcting errors that occur in qubits. This study aims to evaluate the application of QECC to superconducting qubits in improving the stability and accuracy of quantum computing. The method used was a quantitative experiment by comparing the qubit error rate before and after the implementation of QECC, with measurements on bit-flip, phase-flip, and decoherence errors. The results showed that the application of QECC successfully reduced the bit-flip and phase-flip error rates from 15.3% to 5.2% and 12.4% to 4.8%, respectively, while the decoherence decreased from 25.6% to 9.3%. These findings suggest that QECC can significantly improve the stability of quantum computing on superconducting qubits. The conclusion of this study is that the implementation of QECC can be an important step in improving efficiency and accuracy in quantum computing systems, although there are still limitations related to scalability and resources required for deployment in larger systems